2013
DOI: 10.1007/s00705-013-1825-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular differentiation and phylogenetic analysis of the Egyptian foot-and-mouth disease virus SAT2

Abstract: In February 2012, a massive new foot-and-mouth disease (FMD) outbreak struck Egypt. In this work, one-step RT-PCR assays were used for in-house detection and differentiation of foot-and-mouth disease virus (FMDV) in Egypt in this year using pan-serotypic and serotype-targeting sequence primers. FMDV SAT2 was the dominant virus in the examined isolates from the epidemic. The complete VP1 coding regions of two isolates were sequenced. The two isolates had 99.2 % sequence identity to most contemporary Egyptian SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…The results of real time RT-qPCR assays indicated that the serotype responsible for the endemic is SAT2 and confirmed by 716 bp amplified product using RT-PCR. This result agreement with the newly introduced SAT-2 serotype, which has been emerged during February to April 2012 in Upper Egypt (Salem et al, 2012) Delta Governorates (Ahmed et al, 2012 andValdazo Gonzales et al, 2012), Gharbia (Elhaig and Elsheery 2014) and Alexandria (El-Shehawy et al, 2014). Moreover, the failure in detection of serotypes A and O not prevent their implications in field cases (Salem et al, 2012).…”
Section: Discussionsupporting
confidence: 69%
“…The results of real time RT-qPCR assays indicated that the serotype responsible for the endemic is SAT2 and confirmed by 716 bp amplified product using RT-PCR. This result agreement with the newly introduced SAT-2 serotype, which has been emerged during February to April 2012 in Upper Egypt (Salem et al, 2012) Delta Governorates (Ahmed et al, 2012 andValdazo Gonzales et al, 2012), Gharbia (Elhaig and Elsheery 2014) and Alexandria (El-Shehawy et al, 2014). Moreover, the failure in detection of serotypes A and O not prevent their implications in field cases (Salem et al, 2012).…”
Section: Discussionsupporting
confidence: 69%
“…Egypt has been considered to be endemic by A and O FMD strains until 2012 [9] [10] [21]. During 2012/2013, a new extensive FMD outbreak struck Egypt and killed more than 4600 animals and laboratory investigations supported the cause to be the serotype SAT2 [7] [21] [22]. From that time and till now, SAT2 clinically has manifested itself by causing severe clinical disease in cattle and buffalo and no other serotypes were detected [23].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of Sanger-based sequencing and phylogenetic analysis has been instrumental in identifying the source of outbreaks from the distribution of diversity within viral populations (23) since the methodology was first employed to investigate diversity in A and O strains in Europe (24) (Table I). In addition to characterising FMD outbreaks in endemic regions of the world (14,56,57), genomic data have been used recently to characterise FMD viruses recovered from exotic incursions, including the spread of FMD due to serotype SAT 2 into Egypt (58,59), to monitor the spread of lineages into new geographical regions (15,42,60), in the discovery of novel lineages (13,61) and to retrospectively analyse the diversity in previous outbreaks (53,62). Such surveillance highlights the transboundary movements of FMDV, providing critical support for both regional and country-level control programmes.…”
Section: Fig 1 Global Circulation Of Foot and Mouth Disease Virusmentioning
confidence: 99%